Letter to the editor - Tim Bailey (Journal of Applied Animal Nutrition)
Refers to: Wilkinson, J.M. and Young, R.H. Strategies to reduce reliance on soya bean meal and palm kernel meal in livestock nutrition Journal of Applied Animal Nutrition: 8 (2)- Pages: 75 - 82 --- Referred to by: Wilkinson, J.M. and Young, R.H. Response to letter from Tim Bailey Journal of Applied Animal Nutrition: 8 (2)- Pages: 103 - 104